Experimental study on compatibility of reservoir and polymer gel profile control agent - Yang, Sen; Shu, Zheng; Zhang, Qunshuang; Zhao, Yuanshou; Chen, Zongli; Zhang, Lei (Frontiers in Earth Science, 2022)
The coupling relationship between polymer gel system and reservoir pores is an important basis for scientific formulation of tertiary oil recovery programs. The polymer gel profile control agent can significantly modify the fluid migration path inside the reservoir. In this study, artificial cores were used to carry out indoor water flooding experiments after polymer gel injection, considering formation permeability, polymer concentration and polymer injection rate. Based on the accurate records of the breakthrough pressure and injection volume during water flooding, as well as a large number of observations of the microscopic morphology of the cores after the polymer gel profile control and displacement, a set of criteria for determining reservoir-matched polymer gel profile control agents is proposed. The experimental results show that a complex spatial network structure is formed after the gelation of the polymer gel system. As the polymer concentration increases, the network structure of the gel system becomes denser. At the same time, the unit network structure is becoming smaller, and the order of the grid chain structure becomes clearer. Under the condition of low polymer concentration, the backbone structure of the gel is obvious, but there are a lot of fine pores. When the polymer concentration is greater than 1500 mg/L and the injection rate is less than 0.15 ml/min, the water flooding breakthrough pressure is greater than 0.2 MPa, the plugging rate is greater than 95%, and a good plugging effect is obtained.